Dietary bee pollen affects hepatic–intestinal histomorphometry of Nile tilapia fingerlings - Picoli F.* (2019)
© 2019 John Wiley & Sons LtdThe bee pollen is considered an excellent source of flavonoids, carotenoids, phenolic compounds, sterols and minerals; and possesses the ability to boost the immune system, antioxidant action and other interesting therapeutic effects. This study was carried out aiming to evaluate the inclusion of bee pollen in extruded commercial diets of Nile tilapia fingerlings and its effects on the hepatic-intestinal histomorphometry and zootechnical performance. A total of 225 tilapia fingerlings (1.25 ± 0.05 g) were distributed in a completely randomized design in 15 tanks (30 L) maintained in a recirculation water system with three treatments (0% or control, 1.5% and 2.5% of bee pollen inclusion) and five replicates. Feeding rates were defined from the weekly biometrics and periodic monitoring of the physical–chemical water quality parameters. The water quality variables remained within the appropriate range for the species throughout the experiment. There was no significant difference for the somatic indexes and zootechnical parameters in this experiment. However, the inclusion of bee pollen in Nile tilapia fingerlings diets showed a linear increase in hepatocyte morphology (p =.0098). For the intestinal variables of villus height a significant linear increase was observed (p '.05) as the pollen inclusion increased. In fish that received 2.5%, the number of goblet cells was significantly higher (p '.001) than control group and 1.5%. In this sense, the inclusion up to 2.5% bee pollen in extruded commercial diets of Nile tilapia fingerlings had a positive impact on hepato-intestinal histomorphometry without causing negative effects on the zootechnical performance.